Noble morals in Al-Katha's poetry (مجلة جامعة سرت للعلوم الانسانية, 2023)
This study is an attempt to demonstrate the honorable morals in al-Akhtal's poetry and the values ​​and ideals it bears that we Arabs cherish, in addition to the fact that our poet lived through a period of time in which the concepts of poetry changed despite his Christianity and weaving threads of poetry in the court of the Umayyads, as it is considered one of the most important periods in which he flourished. It contains Arabic poetry, and the study took Diwan al-Akhtal as its stage, so the study tended to show its noble morals, such as generosity, courage, chivalry, defense of slander, protection of the tenant, and other honors that we will discuss with study and research, God willing, and we have turned towards this topic because of its great benefit , with regard to what was reported from the honorable morals aspect of its connection to poetry).
Keywords: Noble morals; Morality; Al-Katha's; Umayyad era